Towards a Molecular Understanding of the Fanconi Anemia Core Complex - Charlotte Hodson; Helen Walden (Anemia)
Fanconi Anemia (FA) is a genetic disorder characterized by the inability of patient cells to repair DNA damage caused by interstrand crosslinking agents. There are currently 14 verified FA genes, where mutation of any single gene prevents repair of DNA interstrand crosslinks (ICLs). The accumulation of ICL damage results in genome instability and patients having a high predisposition to cancers. The key event of the FA pathway is dependent on an eight-protein core complex (CC), required for the monoubiquitination of each member of the FANCD2-FANCI complex. Interestingly, the majority of patient mutations reside in the CC. The molecular mechanisms underlying the requirement for such a large complex to carry out a monoubiquitination event remain a mystery. This paper documents the extensive efforts of researchers so far to understand the molecular roles of the CC proteins with regard to its main function in the FA pathway, the monoubiquitination of FANCD2 and FANCI.